Health-related Quality of Life Assessment on 100 Tunisian Patients with Ankylosing Spondylitis using the SF-36 Survey - Azzouz, Dhouha (OMJ, 2012)
OBJECTIVES: The main objective of the study was to examine the self reported health status in patients with ankylosing spondylitis (AS) compared with the general population and the secondary objective (in the AS group) was to study the association between health status, demographic parameters, and specific disease instruments in AS. METHODS: A cross sectional study of 100 AS patients recruited between 2006 and 2009 at the Department of Rheumatology. Health status was assessed by using the SF-36 health questionnaire in patients with AS. Demographic characteristics and disease-specific instruments were also examined by the questionnaire. A sample of 112 healthy individuals was also surveyed using the SF-36 health questionnaire. RESULTS: This study showed a great impairment in the quality of life of patients with AS involving all scales. All male patients with AS reported significantly impaired health-related quality of life on all items of the SF-36 compared with the general population whereas female patients reported poorer health on three items only, namely physical functioning, general health and bodily pain. Mental health was mostly affected than physical role. The physical role was significantly higher in patients with high education level than in patients with low education level (p=0.01). Physical functioning was better in employed patients. All scales of SF-36 were correlated with BASFI, BASDAI and BAS-G. Only physical functioning and general health were correlated with BASMI. CONCLUSION: Impairment in the quality of life can be significant when suffering from AS, affecting mental health more than physical health. Among disease parameters, functional impairment, disease activity, mobility limitation, and spinal pain were the most associated factors resulting to the deterioration of quality of life.